Catheter-Related Acremonium kiliense Fungemia in a Patient with Ulcerative Colitis under Treatment with Infliximab - Fernando A. Díaz-Couselo; Marcelo Zylberman (Case Reports in Infectious Diseases)
Acremonium spp. are filamentous, cosmopolitan fungi commonly isolated from plant debris and soil. They are infrequent pathogens in humans. Acremonium fungemia has been reported in neutropenic patients associated with central venous catheters and in nonneutropenic patients receiving long-term total parenteral nutrition. TNF-α blockade is associated with fungal infections, but no Acremonium spp. infection had been reported up to the present. In this paper, we present a patient with ulcerative colitis who developed Acremonium kiliense fungemia associated with infliximab therapy while receiving total parenteral nutrition. The patient was successfully treated with voriconazole. Acremonium sp. infection must be suspected as another cause of fungal infection in patients under treatment with infliximab.